The DaTa Encryption Based on Discrete Chaotic SYSTEMS AND MAPS - A. V. Sidorenko; K. S. Mulyarchik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The encryption algorithm based on scheme of block symmetric encryption algorithm and used the discrete chaotic systems and maps is presented. Comparative analysis of encryption sets by delayed coordinate method and construction of phase diagrams with famous encryption algorithms based on dynamic chaos is allowed to revealed it’s preferences: increasing of degree defence information, speed and effectiveness of date processing, spreading of functional possibilities in decision cryptography problems. The peculiarities of software and apparatus realization of algorithm are considered.